(untitled) (Bulletin of Armenian Libraries, 2025)
Diplomacy of library culture, as a direction of the state’s foreign policy, implies the exchange of book idea, information, value system, documents, and other elements between different countries and people in order to strengthen the library matter. The term “diplomacy” relates to the ancient Greek word “diploma”, which means “a double-folded document containing official agreements, decisions”. In addition to political diplomacy, there is also second-track diplomacy, i.e. non-governmental, unofficial connections and activities between private citizens or groups of individuals. It is also important the modern international digital diplomacy and its implementation through global social networks. Unlike traditional diplomacy, digital diplomacy works differently by facilitating access to knowledge, bridging exchanges between scientific research and policy. In the article, an attempt was made to define the place of international activity of libraries in the system of international relations of culture. In addition, to develop the work of libraries with foreign libraries and librarian associations, specialized cultural, informational, educational, scientific organizations and institutions.